Behavioral tests assessing neuropsychiatric phenotypes in adolescent mice reveal strain- and sex-specific effects - Eltokhi, Ahmed; Kurpiers, Barbara; Pitzer, Claudia (Scientific reports, 2020)
In humans, infancy and adolescence are associated with major changes in synaptic functions and ongoing maturation of neural networks, which underlie the major behavioral changes during these periods. Among adult cases with neuropsychiatric disorders including autism spectrum disorder, schizophrenia, attention deficit hyperactivity, and bipolar disorders, 50% have developed behavioral symptoms and received a diagnosis before 15 years of age. However, most of the behavioral studies in mice modeling neuropsychiatric phenotypes are performed in adult animals, missing valuable phenotypic information related to the effect of synaptic maturation during development. Here, we explored which behavioral experiments assessing neuropsychiatric phenotypes can be performed during a specific window of development in adolescent male and female C57BL/6N, DBA/2, and FVB/N mice that are typically used as background strains for generating genetically-modified mouse models. The three wild-type strains were evaluated across anxiety, social behaviors, and cognitive functions in order to cover the main behavioral impairments that occur in neuropsychiatric disorders. During adolescence, the three strains displayed significant differences under certain behavioral paradigms. In addition, C57BL/6N and FVB/N, but not DBA/2 mice revealed some sex-related differences. Our results provide new insights into discrete behaviors during development and emphasize the crucial importance of the genetic background, sex, and experimental settings in the age-dependent regulation of different behaviors.
Gesehen am 10.08.2020